Comparison on dimensional accuracy using a newly developed nozzle for open-source 3D printer - Sukindar, Nor Aiman; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B.T. Hang Tuah; Jaafar, Che Nor Aiza; Ismail, Mohd Idris Shah (Trans Tech Publication, 2016)
Fused Deposition Modeling (FDM) or also known as RepRap (Replicating Rapid Prototyper) is a technology that is synonym with 3D printing. This technology has entered a new era with an increasing demand among the community. It has grown commercially in the market of open-source system and it is relatively low cost. Many efforts have been put towards the development of the system in both hardware and software to increase the quality and the performance. The research highlights the development of a new nozzle to evaluate the performance on dimensional accuracy in comparison to the original nozzle. The nozzle emphasizes the die angle for the polylactic acid (PLA) material, the liquefier design which provide constant heat in the liquefier chamber, as well as insulator for the liquefier using highly insulated material. The dimensional accuracies of both nozzles were compared where the result showed that the new nozzle provided better accuracy and stability on the extruding PLA material.